Just Bananas? Fair Trade Banana Production in the Dominican Republic - Shreck, Aimee (The International Journal of Sociology of Agriculture and Food, 2021)
In an effort to alter exploitative relations that characterize the conventional agro-food system, Fair Trade organizations are promoting an alternative system of certification and labeling for commodities such as coffee, cacao, and bananas that are grown under healthy social and environmental conditions. Labels then identify these products to conscientious consumers who are willing to pay more for them with the expectation that higher prices will deliver additional returns to producers. Yet, do these initiatives offer a real alternative and can they foster positive social change in the agro-food system? Drawing on fieldwork in the Dominican Republic, this paper addresses the implications of Fair Trade at the level of production. I focus on a case study of a certified banana producer group to suggest that production for the Fair Trade market can provide much needed material benefits, strengthen the producers’ organization, and open up critical market access to Fair Trade partners. However, I also discuss important limits to the broader potential of Fair Trade initiatives for transforming trade relations. Fair Trade should not be ignored as an alternative mode of production or trade but, rather, a better understanding of how they are experienced by producers can help address the limits of the initiatives.